Are Treble Damages Neutral? Sequential Equilibrium and Private Antitrust Enforcement - Besanko, David; Spulber, Daniel F. (American Economic Review, 1990)
A sequential equilibrium model of private antitrust enforcement is presented. Consumers have incomplete information about cartel costs and cannot accurately estimate a priori the damage recovery from an antitrust action. Consumers are able to infer cartel costs from the equilibrium pricing strategy of firms. The universal divinity criterion is used to characterize the sequential equilibrium. It is shown that for a sufficiently large damage multiple, antitrust enforcement effectively increases social welfare.